Montage, Memories, Machine - Jasmin Pfefferkorn (Media Theory)
This paper explores the entanglement of human perception and machine operations in contemporary photographic culture, using montage as a conceptual resource to interrogate our understanding of photography in the context of computational vision and algorithmic culture. It takes as a key example the ‘Memories’ feature of the Apple Photos application, in which ‘For You’ albums organize and (re)present images from a personal camera roll back to the viewer-user as a slideshow montage. Through a combination of technical analysis and auto-ethnography, it argues that the relation between stillness and motion in this instantiation of montage offers a productive way of understanding what it means to ‘see photographically’ within the contemporary socio-technical assemblages that comprise digital photography.